Seroprevalence of SARS-CoV-2 virus antibodies and sociodemographic features of pregnant women in Mogadishu, Somalia: a cross-sectional survey study - Maryan Abdullahi Sh. Nur; Hassan Abdullahi Dahie; Nima Abdi Hassan; Bashiru Garba; Jamal Hassan Mohamoud; Najib Isse Dirie; Mohamed Hussein Adam (BMJ Open)
Objective Recent investigations have revealed that COVID-19 during pregnancy substantially increases the risk of harmful outcomes for mothers and neonates, including preterm death and stillbirth as well as severe maternal morbidity and mortality. Hence, the urgent need to understand the prevalence rate and level of awareness about COVID-19 (SARS-CoV-2 virus infection) and the practice of preventive measures against the disease among pregnant women in Somalia. This study aims to determine the prevalence of COVID-19 among pregnant women seeking antenatal care in the Benadir region (Mogadishu) of Somalia and to assess their knowledge and preventive practices towards COVID-19.Setting A hospital-based cross-sectional study involving two major referral maternity hospitals in Mogadishu, Somalia.Participants Pregnant women seeking antenatal services were included in our study.Methods A total of 477 blood samples were collected from pregnant women attending the two referral hospitals in Mogadishu and screened for COVID-19. The participants were subjected to questionnaire interviews where their detailed history and practice of prevention against COVID-19 were evaluated.Results The results showed that 175 (36.7%) were positive while 302 (63.3%) samples were negative for SARS-CoV-2 virus antibodies. Also, out of the 141 pregnant women who had two children or less, 19.4% were positive for IgG/IgM antibodies. Participants who had close contact with patients with COVID-19 were significantly associated for testing positive with a p value 0.0001. Students, teachers, employed people and individuals reported COVID-19 like symptoms were all associated with COVID-19 seropositivity outcomes.Conclusion Pregnant women and those with commorbidies should be given special preventive care and health education about COVID-19 transmission.